Discontinuation of imatinib in Japanese patients with chronic myeloid leukemia - Takahashi, Naoto (Ferrata Storti Foundation, 2012)
It was recently recognized that some chronic myeloid leukemia patients with a complete molecular response could sustain that response after discontinuation of imatinib. To characterize the clinical outcomes and profiles of chronic phase chronic myeloid leukemia patients who could discontinue imatinib, we conducted a nationwide survey in Japan. Among 3,242 imatinib-treated chronic myeloid leukemia patients, we identified 50 who had discontinued imatinib for at least six months; of these we analyzed 43. Molecular recurrence was detected in 19 patients, and a complete molecular response rate was estimated to be 47% following imatinib discontinuation. Based on multivariate regression analysis, imatinib dose intensity and prior interferon-α administration were independently predictive of molecular recurrence within 12 months. The depth of the molecular response should be a factor influencing long-term sustained complete molecular response after discontinuation of imatinib. Additionally, an immunological mechanism modified by interferon-α might control chronic myeloid leukemia stem cells.